TEKNIK PENERJEMAHAN HUMOR GELAP (DARK JOKES) BAHASA JERMAN PADA TAKARIR BERBAHASA INDONESIA FILM BUBA - Putri, Maya Syafira Harfiani; Syahida, Ilma Aghnia Ali; Rahma, Salwa Awalia (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2024)
The research titled "Translation Technique Of German Dark Jokes In The Indonesian Subtitle Of Buba Movie" explores techniques for translating dark jokes from German into Indonesian subtitle. Given their subtlety and controversy, dark jokes pose significant cross-cultural and linguistic challenges. By examining examples from the movie Buba and its Indonesian subtitles, the study assesses translation techniques to maintain humor and original intent while ensuring comprehension. The findings highlight the importance of cultural context and linguistic creativity in translating dark humor. The study identified instances of humor: universal and cultural including ethnic or multicultural, and reality-based. Translation strategies based on Molina and Albir's (2002) theory included borrowing, linguistic compressions, literal translations, transposition, particularization, linguistic amplification, modulations, and discursive creation.